Geolokasi Penderita Hipertensi di Wilayah Pinggiran Sungai Martapura - hammad, hammad (Jurnal Skala Kesehatan, 2025)
The purpose of this study is to determine the geolocation of hypertension in the Sungai Martapura pinggiran, specifically in Sungai Rangas Ulu and Sungai Rangas Hambuku. This study uses a quantitative approach with a survey design. About 90 respondents were selected using a simple random sampling method, and the data was collected using a questionnaire and analyzed using the Hypertenstrack application. The results indicate that the prevalence of hypertension is not consistent in the relevant area, indicating that it is present in every study area. This highlights the importance of universal health interventions, not just those based on risky locations. In addition, risk factors like lanjut usage, unhealthy eating habits, and a lack of physical activity are also considered to be contributing factors to dominance. This geospatial information can serve as a foundation for more accurate and timely promotion and prevention efforts.